Future direction of digital textbooks in undergraduate nursing education: A scoping review - Aeri Jang; Hyunyoung Park; Jeong Eun Moon (PLoS ONE, 2025)
Digital natives have emerged, and nursing educator must develop digital textbook(DT)s the meet their information processing methods. But literature reviews on DTs remain insufficient. This scoping review aims to guide nursing educators on the future direction of DTs in undergraduate nursing education. This study includes research on DTs published in English after 2016, targeting undergraduate nursing students. Two reviewers independently screened titles, abstracts, and full texts for inclusion and extracted data from Medline (PubMed), Embase (Elsevier), Cochrane Library, Cumulative Index to Nursing and Allied Health (CINAHL), and IEEE Xplore up to May 27, 2024. Of the 3,978 articles identified, 7 met the inclusion criteria. The most common study design was experimental (n = 5), and the most frequent intervention type was interactive (n = 5). The most common nursing field was caring for medically complex/special needs patients (n = 5). However, no DTs were developed for social determinants of health or mental health or for working in underserved communities. Information was provided via mobile devices (n = 2) and QR codes, applications, or links (n = 2). Six studies measured all three outcome variables: knowledge, skills, and attitudes. The technology aspects included feedback, display functions, and other technical and educational features. The findings highlight the importance of usability, integration with the nursing education curriculum, and the development of clinically based DTs for future undergraduate nursing education. Thus, DTs in undergraduate nursing education, designed for the digital native generation, should be developed based on interactive intervention-type content that facilitates easy access to personalized information and timely learning. In addition, to comprehensively cover the educational domains essential for future nurses, DTs should not only address caring for medically complex/special needs patients but also include content on social determinants of health, mental health, and nursing in underserved communities.